Motives and Barriers to Exercise among Underweight Filipino College Students - Manasan, Patrick L.; Quitor, Cristine G.; Ronquillo, Vincent P.; Dabu, Darelle C.; Dela Cruz, Jennilyn T.; Sode, Ma. Angela V.; Cruz, Salvador Jr. L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
In many cases, underweight students may be left behind due to poor nutrition, health issues, or lack of access to resources that would help them thrive and achieve their academic goals. This condition is often overlooked, but it can have serious health consequences. In this paper, the researchers used the free-listing method to ascertain the perceived motives and barriers to exercise among underweight Filipino university students. This quantitative-descriptive study comprised 300 underweight Filipino college students enrolled in ‘PATHFIT-2: Exercise-Based Fitness Activities' for first-year students during their Second Semester of the Academic Year 2022-2023 from the main campus of a state university in Pampanga, Philippines, who were classified as having BMIs below the normal weight. Furthermore, EMI-2 from Mullan et al. (1997) subscales were used to categorize responses in the free list for motives, whereas Myers and Roth's (1997) subscales were utilized to categorize barriers. The top five reported motives for underweight students were "positive health," "strength and endurance", "ill health avoidance", "appearance", and "weight management". While "competition", "nimbleness", "affiliation", and "health pressures" did not elicit a response. On the other hand, most respondents do not have enough time and are too lazy to exercise since it may interfere with their school-related tasks. The findings provided educational institutions with precise recommendations on how to establish exercise programs that are in line with what motivates students and examine any barriers that may prevent such physical activity engagement.